2020
DOI: 10.3390/pharmaceutics12121133
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Fluvastatin as an Anticancer Agent against Breast Cancer Stem Cells via Encapsulation in a Hyaluronan-Conjugated Liposome

Abstract: Fluvastatin (FLUVA), which is a common anti-hypercholesterolemia drug, exhibits potential anticancer activity as it suppresses the proliferation, angiogenesis, and metastasis of breast cancer cells via inhibiting 3-hydroxy-methyl glutaryl-coenzyme A (HMG-CoA) reductase. In this study, hyaluronan-conjugated FLUVA-encapsulating liposomes (HA-L-FLUVA) were evaluated for their anticancer efficacy in vitro and in vivo. The particle size, zeta potential, and encapsulation efficiency of HA-L-FLUVA were 158.36 ± 1.78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Breast cancer stem cellxenografted mouse model [129] HA-coated silica/hydroxyapatite-DOX HA-coated inorganic nanoparticles CD44-targeted 4T1 tumor-bearing mice [130] HA-sclareol/poly-lacticco-glycolic acid HA-coated inorganic nanoparticles CD44-targeted, hydrophilic MCF-7 and MDA-MB468 cell lines [131] HA-coated camptothecin HA-coated inorganic nanoparticles CD44-targeted MDA-MB-231 cells [132] HA and poly-(N-εcarbobenzyloxy-Llysine)…”
Section: Polymeric Nanoparticles Cd44-targeted Hydrophilic Barriermentioning
confidence: 99%
“…Breast cancer stem cellxenografted mouse model [129] HA-coated silica/hydroxyapatite-DOX HA-coated inorganic nanoparticles CD44-targeted 4T1 tumor-bearing mice [130] HA-sclareol/poly-lacticco-glycolic acid HA-coated inorganic nanoparticles CD44-targeted, hydrophilic MCF-7 and MDA-MB468 cell lines [131] HA-coated camptothecin HA-coated inorganic nanoparticles CD44-targeted MDA-MB-231 cells [132] HA and poly-(N-εcarbobenzyloxy-Llysine)…”
Section: Polymeric Nanoparticles Cd44-targeted Hydrophilic Barriermentioning
confidence: 99%
“…Simvastatin induces glutathione (GSH)-mediated suppression of ABCG4 (which causes efflux of intracellular doxorubicin and cisplatin) levels, increasing the sensitivity of prostate cancer cells to doxorubicin or cisplatin and leading to the suppression of tumor growth and size without doxorubicin-induced cytotoxicity [ 98 ]. An in vivo tumor xenograft model of breast cancer showed that encapsulation of fluvastatin in a hyaluronan-conjugated liposome and administration with doxorubicin produced a potent anti-proliferative effect with the longest survival in mice [ 99 ]. Atorvastatin sensitizes the anti-cancer effect of doxorubicin and cisplatin in human osteosarcoma by suppressing matrix metalloprotease 2 (MMP2) induced by doxorubicin and cisplatin [ 100 ].…”
Section: Statins Possess Synergistic Action To Overcome the Resistance To Anti-cancer Therapiesmentioning
confidence: 99%